2023
DOI: 10.1002/ajb2.16113
|View full text |Cite
|
Sign up to set email alerts
|

Pollen‐feeding behavior of diverse insects on Geranium delavayi, a flower with large, accessible pollen grains

Abstract: Premise: Why have pollen grains evolved to be exceptionally large in some species? Pollen-feeding hypothesis suggests that if the proportion of pollen amounts for feeding is reduced in a flower, the low allocation to pollen number would allow pollen grains to be larger. Methods: To examine whether species with large pollen grains experience low pollen consumption, the behavior of insects feeding on nectar and pollen was observed and pollen transfer efficiency was estimated for four visitor types in Geranium de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A comparative study of honeybee and bumblebee honeys from different geographical and botanical origins reported a similar qualitative composition of free AAs between the two types of honeys, although the quantitative composition was different [ 56 ]. Another comparative study reported recently that honeybees and bumblebees both avoid foraging nutritionally poor (e.g., having low protein and high lipid content) and highly toxic pollen, compared to other insects [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…A comparative study of honeybee and bumblebee honeys from different geographical and botanical origins reported a similar qualitative composition of free AAs between the two types of honeys, although the quantitative composition was different [ 56 ]. Another comparative study reported recently that honeybees and bumblebees both avoid foraging nutritionally poor (e.g., having low protein and high lipid content) and highly toxic pollen, compared to other insects [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The macroscopic and microscopic morphological characteristics of flowers can play an important role in the classification of Geranium [ 17 ]. In addition, many studies have shown that the flower morphology of Geranium has a significant impact on flower evolution and pollination behavior [ 18 , 19 , 20 , 21 ]. However, detailed research on the early development of mixed buds and flower buds in G. koreanum has not been reported.…”
Section: Introductionmentioning
confidence: 99%